Here is a table : a philosophical essay history and race/ism - Dladla, Ndumiso (African Sun Media, 2020)
"Our understanding of racism is that it is the systematic doubt concerning the humanity of the other. It is a means to an end, namely, to pursue the dehumanisation of the other for one's sole and exclusive benefit. The doubt is in itself ethically indefensible. Yet, it ultimately acquires the status of an incontrovertible truth around which economic and political life is organised and conducted. This has been and continues to be the reality in South Africa today. The hypothesis of this book is that a philosophical-historical study of racism will reveal that it has only ever been and continues to be white supremacy. In South Africa the actuality of the doubt is that it has always arisen from one side ("whiteness") and directed itself against the other ("blackness"). Our purpose is to show that racism properly speaking is white supremacy and that it cannot be properly understood without African philosophy."--Page 4 of cover.